2007
DOI: 10.1186/1471-2199-8-104
|View full text |Cite
|
Sign up to set email alerts
|

The DeoR-type transcriptional regulator SugR acts as a repressor for genes encoding the phosphoenolpyruvate:sugar phosphotransferase system (PTS) in Corynebacterium glutamicum

Abstract: Background: The major uptake system responsible for the transport of fructose, glucose, and sucrose in Corynebacterium glutamicum ATCC 13032 is the phosphoenolpyruvate:sugar phosphotransferase system (PTS). The genes encoding PTS components, namely ptsI, ptsH, and ptsF belong to the fructose-PTS gene cluster, whereas ptsG and ptsS are located in two separate regions of the C. glutamicum genome. Due to the localization within and adjacent to the fructose-PTS gene cluster, two genes coding for DeoR-type transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 61 publications
5
95
0
Order By: Relevance
“…No PCR product was obtained when reverse transcriptase was omitted. From this experiment we concluded that sugR and cg2116 were organized as an operon, an observation that was also reported by Gaigalat et al (2007).…”
Section: Features Of Sugr Transcription and Expressionsupporting
confidence: 84%
See 1 more Smart Citation
“…No PCR product was obtained when reverse transcriptase was omitted. From this experiment we concluded that sugR and cg2116 were organized as an operon, an observation that was also reported by Gaigalat et al (2007).…”
Section: Features Of Sugr Transcription and Expressionsupporting
confidence: 84%
“…Gaigalat et al (2007) suggested that SugR may be able to form complexes with individual binding sites with different sensitivities to sugar phosphates as described for the TrmB regulator of Pyrococcus furiosus (Lee et al, , 2007, and proposed mutational analyses of the SugR-binding sites to clarify this issue. Prior to this analysis, however, SugR binding on its various targets under the same in vitro binding conditions and with a native SugR protein should be analysed.…”
Section: Identification Of Sugr Co-inducersmentioning
confidence: 99%
“…The levels of bglF and bglF2 mRNAs did not increase upon the addition of glucose or fructose. This indicates that the regulatory mechanism of bglF and bglF2 is different from that of pts genes that are controlled by the transcriptional repressor protein SugR (Engels & Wendish, 2007;Gaigalat et al, 2007;Tanaka et al, 2008b). Indeed, we found that bglF and bglF2 mRNA levels did not increase upon the disruption of sugR gene (data not shown).…”
Section: Regulation Of Bglf2 Expression By B-glucosidesmentioning
confidence: 71%
“…However, it is interesting to note that the effects of inactivation of these regulators in any combinations tested on the ramA promoter activity appeared to be unaffected by the carbon source used. Because SugR represses genes involved in sugar uptake and metabolism in the absence of sugar and its repressor activity is inhibited by sugar metabolites (32,35,36,55), the degree of derepression of most SugR target genes in the sugR mutant is higher in the absence of sugar than in its presence. However, the degree of derepression of ramA promoter activity in the sugR mutant in the presence of glucose was comparable to that in the presence of acetate.…”
Section: Discussionmentioning
confidence: 99%
“…For example, expression of the gapA-pgk-tpi operon, encoding the glycolytic enzymes glyceraldehyde-3-phosphate dehydrogenase, phosphoglycerate kinase, and triose phosphate isomerase, respectively, is coordinately regulated by SugR, RamA, and GlxR (15,31,32). SugR is a global repressor of genes for sugar uptake and metabolism, including phosphotransferase systems, glycolysis, and fermentative lactate dehydrogenase (32)(33)(34)(35)(36)(37). As sugar phosphates, e.g., fructose-1-phosphate and fructose-1,6-bisphosphate, act as negative effectors of SugR, the SugR regulon is derepressed in the presence of sugar.…”
mentioning
confidence: 99%